Implementation of Total Quality Management and ISO 9000 Certification - Foo, Weng Kar; Muhammad Afiq, Yusof; Sorooshian, Shahryar; Syed Radzi, Rahamaddulla (IJEAST, 2016)

(untitled)
In this article, we studied on business performance after the implementation of total quality management (TQM) and ISO 9000. Researchers claimed that ISO certification will improve business performance and outcomes. They also believe that ISO 9000 will be necessary to stay in business in the future. Motives of organization toward ISO 9000 are very important. Benefits and difficulties faced during the implementation of TQM and ISO 9000 will be discussing in further. This paper states that quality management system proposed by ISO 9000 is a necessary foundation for other quality methods.